The Mesohellenic trough and the Thrace Basin. Two Tertiary molassic Basins in Hellenides: do they really correlate? - Kilias, Ad.; Vamvaka, A.; Falalakis, G.; Sfeikos, A.; Papadimitriou, E.; Gkarlaouni, Ch.; Karakostas, B. (Bulletin of the Geological Society of Greece, 2013)
Based on lithostratigraphic and structural data, as well as geological mapping, the mollasic Thrace Basin (ThB) in NE Greece (including the Paleogene deposits of the Axios Basin) was compared with the Mesohellenic Trough (MHT) in NW Greece. Both basins are characterized by a thick sedimentary sequence of molassic-type strata (3-5km thickness) of Tertiary age, overlain unconformably by Miocene- Pliocene and Quaternary deposits. Molassic sedimentation started almost simultaneously in both areas during the Mid-Upper Eocene but it finished in different time, in the Mid-Upper Miocene for the MHT and the Upper Oligocene for the ThB, respectively. Sedimentation in ThB was also linked with an important calc-alkaline and locally shoshonitic magmatism of Eocene-Oligocene age. We interpreted the MHT as a polyhistory strike-slip and piggy-back basin, above westward-emplacing ophiolites and Pelagonian units on the cold Hellenic accretionary prism. In contrast to MHT, the ThB evolved as a Paleogene supra-detachment basin above the strongly extended during the Eocene-Oligocene Hellenic Hinterland. The syn-depositional magmatic products, linked possibly with subduction processes in Pindos or Axios ocean(s). In any case, MHT and ThB are related to inferred oblique convergence of the Apulia plate and the internal Hellenic units.